Determining the Best Rainwater Harvesting System in Al-Muthanna Governorate, Iraq - Al-Khafaji, Dhuha S.; Abdulkareem, Asraa Khtan; Al-Kubaisi, Qusai Y. (Iraqi Journal of Science, 2022)
Rainwater harvesting is one of the available solutions to overcome water scarcity in arid and semi-arid regions with highly variable rainfall and unexpected periods of drought or floods. This study aims to identify the best rainwater harvesting system in Al-Muthanna governorate using Remote Sensing (RS) and Geographic Information System (GIS) techniques. Landsat 8 images were used to produce the land use map which shows five different classes: water (0.2%), bare soil (82.11%), built-up (15.71%), forest (0.27%), and farmland and grass (1.71%). The results revealed that the rainwater harvesting system can be applied only in the north and north-eastern parts of the study area which consists of residential and agricultural areas and has a maximum monthly mean rainfall range of (85.32-157.21) mm. Rooftops, semi-circular bunds, and ponds are the most suitable systems for rainwater harvesting in Al-Muthanna. The rooftops system can provide 7000-13,500 litres of water for domestic purposes. Furthermore, if the water quality was low, it could be also used in agriculture practices or  to irrigate home gardens.